2011
DOI: 10.1051/radiopro/20116457s
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide speciation in sediments of the Yenisei River

Abstract: Abstract. The examination of sediment samples collected from the Yenisei River revealed the presence of artificial radionuclides characteristic of radioactive discharges from the MCC facility: isotopes of europium ( 152 Eu, 154 Eu, and 155 Eu), cesium ( 137 Cs and 134 Cs), 60 Co, 90 Sr, and transuranium elements. Radionuclide concentrations in sediment layers remained high as far as 240 km downstream of the MCC. The vertical distribution of radionuclides in sediment cores was very complex, and down-core varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Detailed radioecological studies of the Yenisey focusing on the contamination of water and sediments started only in the 1990s and were most frequent in the last decade (Sukhorukov et al 2000;Bondareva and Bolsunovskii 2008;Bondareva and Artamonova 2011;Sukhorukov et al 2004Sukhorukov et al , 2006Linnik et al 2005Linnik et al , 2006Vakulovsky et al 2006Vakulovsky et al , 2014Bolsunovsky 2011;Kropatcheva et al 2012;Korobova et al 2014). The main practical goal of these studies was to evaluate the level and extent of contamination and its radioecological significance.…”
Section: Introductionmentioning
confidence: 97%
“…Detailed radioecological studies of the Yenisey focusing on the contamination of water and sediments started only in the 1990s and were most frequent in the last decade (Sukhorukov et al 2000;Bondareva and Bolsunovskii 2008;Bondareva and Artamonova 2011;Sukhorukov et al 2004Sukhorukov et al , 2006Linnik et al 2005Linnik et al , 2006Vakulovsky et al 2006Vakulovsky et al , 2014Bolsunovsky 2011;Kropatcheva et al 2012;Korobova et al 2014). The main practical goal of these studies was to evaluate the level and extent of contamination and its radioecological significance.…”
Section: Introductionmentioning
confidence: 97%
“…The radiochemical plant and other MCC facilities are still operating. Several scientific expeditions revealed that the Yenisei River floodplain is contaminated with artificial radionuclides, including plutonium isotopes, within 2000 km downstream of the MCC Klemt et al, 2002;Bolsunovsky & Bondareva, 2007;Bolsunovsky, 2010Bolsunovsky, , 2011Bolsunovsky & Dementyev, 2010;Semizhon et al, 2010). Since 1995, researchers of the Institute of Biophysics (Krasnoyarsk) and the Institute of Geology and Mineralogy (Novosibirsk) have found radioactive particles in floodplain soils and sediments during their sampling campaigns at the Yenisei (Bolsunovsky & Tcherkezian, 2001;Bolsunovsky, 2009;Chuguevskii et al, 2010).…”
Section: Introductionmentioning
confidence: 99%